Extending The Vase Life of Peruvian Lily (Alstroemeria Spp.) With 1‐Methylcyclopropene and Ascorbic Acid - Obadamudalige, B.S.; Beneragama, Chalinda Koshitha; Mawalagedera, S.M.M.R. (International Journal of Applied Sciences and Biotechnology, 2019)
Alstroemeria spp. is one of the highly demanded cut flower in the local and global cut flower market. Short vase life of flowers and leaves, petal wilting, petal drop, and transparency of petals are major postharvest problems. The objective was to extend the vase life of Alstroemeria spp. with 1-methylcyclopropene and ascorbic acid. Freshly cut flowering stems of Alstroemeria spp. were treated with 1-methylcyclopropene (0.25 ppm) and ascorbic acid (57 mM) alone and in combination of the two, for six hours. Distilled water was used as the control. Postharvest concentrations of anthocyanin, chlorophyll and glucose in flowers were best maintained when treated with a combination of 1‐methylcyclopropene and ascorbic acid, compared to all other treatments. Percentage fresh weight loss was same among treatments. The best treatment to extend vase life of Alstroemeria spp. is the combination of 1‐methylcyclopropene and ascorbic acid, which extended the vase life by additional seven days compared to the control. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 174-183